Una pedagogia per l’età “planetaria” - Saccardi, Severino (Studi sulla Formazione/Open Journal of Education, 2024)
Born in Santa Fiora, a mining village on Monte Amiata, Ernesto Balducci realised from his own life experience the meaning of education and culture for the redemption of the oppressed. For his ideal journey ‘from the village’ (including its values of solidarity and justice) to the ‘planetary age’ his social and human roots were utterly significant. In spite of the diversity of their life experiences, there are obvious parallelisms between Ernesto Balducci’s and Don Lorenzo Milani’s message, as both intended to contribute culturally and pedagogically to the shaping of a new and conscious ‘citizens of the world’.